SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN REWARD TEKNISI PADA PT. TELKOM AKSES MENGGUNAKAN METODE TOPSIS - Sasongko, Jati; SAIFUDIN ZUHRI, ALFAD (Information Technology and Telematics, 2018)
Abstract- PT. Telkom Access requires a decision support system that can determine which technicians have priority to get a salary based on their performance and productivity and can determine the amount of bonus that the technician deserves. This decision support system can also be useful to monitor the performance of technicians from time to time. This system can also be used as a reference in determining the next steps for outstanding technicians or not. The analytical method uses the Technique For Order Preference method by Similarity to Ideal Solution (TOPSIS), the system development method used in this research is web engineering consisting of formulation, planning, analysis, engineering using UML, implementation using PHP and MySQL.The final result of this study is the result of a decision support system for giving reward technicians to PT. Telkom Access using the TOPSIS method is a technician who gets a reward is a technician who has the highest final value in light green while the lowest rated technician is pink